2003
DOI: 10.1001/archpsyc.60.7.702
|View full text |Cite
|
Sign up to set email alerts
|

A Twin Study of the Genetics of Fear Conditioning

Abstract: Genes represent a significant source of individual variation in the habituation, acquisition, and extinction of fears, and genetic effects specific to fear conditioning are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 35 publications
6
108
0
1
Order By: Relevance
“…In a prior analysis, we demonstrated that the electrodermal skin conductance response (SCR) amplitudes seen in response to the habituation, acquisition, and extinction components of the classical fear conditioning paradigm are moderately heritable and share a substantial proportion of their underlying genetic factors (17). Similarly, Crider et al showed that nonspecific electrodermal response (EDR) lability and speed of habituation exhibited genetic covariation, with heritability similar to our estimate for SCR (40-50%).…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…In a prior analysis, we demonstrated that the electrodermal skin conductance response (SCR) amplitudes seen in response to the habituation, acquisition, and extinction components of the classical fear conditioning paradigm are moderately heritable and share a substantial proportion of their underlying genetic factors (17). Similarly, Crider et al showed that nonspecific electrodermal response (EDR) lability and speed of habituation exhibited genetic covariation, with heritability similar to our estimate for SCR (40-50%).…”
Section: Introductionsupporting
confidence: 83%
“…The second (A 2 ) models associative learning that takes place during the fear conditioning process in the acquisition and extinction phases, which may also be shared with SRF. These two reflect our prior finding that two genetic factors are sufficient to account for individual differences in the five electrophysiologic response variables (17). Finally, we postulated a third factor (A 6 -corresponding to the sixth measured variable, SRF) that accounts for individual variation in self-report fears not accounted for by the factors explaining the electrophysiologic responses.…”
Section: Statistical Analysessupporting
confidence: 71%
See 2 more Smart Citations
“…We excluded studies that depended on electrodermal skin conductance (i.e., Hettema, Annas, Neale, Kendler, & Fredrikson, 2003) or other non-specific diagnostic tools without additional psychological assessment. Literature reviews were excluded.…”
Section: Methodsmentioning
confidence: 99%